Antimicrobial resistance patterns of Staphylococcus aureus isolated from apparently healthy pet cats of Bangladesh - Das, Shanta; Kabir, Ajran; Chouhan, Chandra Shaker; Shahid, Md Ahosanul Haque; Habib, Tasmia; Kobir, Md Alamgir; Hossain, Md Zawad; Rahman, Marzia; Nazir, K H M Nazmul Hussain (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study sought to determine the occurrence, molecular identification, antimicrobial-resistant trends, and gene distribution of Staphylococcus aureus in pet cats and their owners’ hand swabs. Materials and Methods: From different places and clinics in Mymensingh and Dhaka, 168 pet cat samples and 42 hand swab samples from cat owners were obtained. The organisms were scrutinized by assessing the outcomes using conventional and molecular techniques. The disc diffusion technique was applied to find the resistance pattern against 12 antibiotics, and genes were discovered by targeting specific genes using PCR. Results: The occurrence of pathogenic S. aureus in pet cats was 7.74%, while it was 9.50% in pet owners’ hand swabs, and 25.0% of the pet owner’s hand swabs contained these genes. Staphylococcus aureus was utterly resistant to amoxicillin, ampicillin, cefixime, erythromycin, and imipenem in both pet cat and hand swabs of pet owner samples. All S. aureus isolates had a multidrug-resistant phenotype, and 1 from pet cats (O19) and 1 from pet owner hand swabs (H9) were resistant to all 12 antibiotics in the 7 antimicrobial classes. Several antibiotic-resistance genes were detected by PCR. Conclusion: The study confirmed multidrug-resistant pathogenic S. aureus in pet cats and their owners in Bangladesh, indicating a major health risk to both people and cats. Thus, a holistic and integrated one-health approach between veterinary and medical specialists is needed to mitigate the global distribution of these zoonotic antibiotic-resistant S. aureus strains. J. Adv. Vet. Anim. Res., 10(3): 545–553, September 2023 http://doi.org/10.5455/javar.2023.j708